Changing with the Times: Report on School Leadership in a Society in Transition - Muhammad Othman Alhuzaim; Omar Elmoussa; Maura A. E. Pilotti (MDPI AG, 2022)
The present study examined the status of leadership in the secondary education sector of a society in transition from an economic engine based on tribal ties and oil production to one that is diversified and meritocratic. It focused on high schools as one of the focal points of top-down interventions intended to promote social change. The study relied on the MLQ-5x to collect the views of leadership styles and outcomes that high-school leaders (principals) attribute to themselves and that constituents (teachers) attribute to them. A stratified random sample of high schools in the eastern region of Saudi Arabia was tested. In this study, transformational leadership was the prevailing style for both leaders' self-attributions and constituents' attributions, suggesting that change is now an accepted notion. However, only a moderate level of agreement existed between leaders and constituents on the actual persons who embody it, thereby indicating that the translation of abstract ideas into practical realities is a work in progress.